Cosmopolitisme au pluriel - Alessandra Siqueira Barreto; Rogéria Campos de Almeida Dutra (Ateliers d'Anthropologie)
This article considers the question of cosmopolitanism in the contemporary world, stressing the anthropological perspective and situating forms and practices of coexistence relations between people from different backgrounds through the cultural and political mediation developed by a Brazilian religious leader on European soil. This immigrant’s trajectory serves as a basis for considering important questions like migratory processes, the relation between individual and collective projects, and the ambiguity between asserting world citizenship by constructing a transnational political project and maintaining local connections that in some cases underpin exclusion rhetoric. Finally, the article offers a few thoughts on the relation between cosmopolitanism and cosmopolitics, and ponders the possibility of being able to speak in terms of global citizenship.